Two new species of Agonopterix (Depressariidae, Lepidoptera) from Europe - Buchner, Peter (Zootaxa, 2015)
The species Agonopterix tripunctaria sp. nov. and Agonopterix medelichensis sp. nov. are described. A. tripunctaria, previously misidentified as Agonopterix nodiflorella (Millière, 1866), was recognized as specifically different by the distinctive male genitalia. 19 specimens have been examined, DNA-barcoding yielded full 658 bp fragment of COI from two specimens and a 639 bp sequence from a third, confirming the impression of a rather isolated species. Specimens from Italy, Slovenia, Croatia and Greece had been checked, among them one reared from Ferulago campestris. A. medelichensis was misidentified as Agonopterix rotundella (Douglas, 1846) in NHMV; its male genitalia are erroneously depicted as A. rotundella in Hannemann (1953) and (1995). 20 specimens have been examined, from one a 555 bp fragment of COI was obtained, confirming that it is not closely related to A. rotundella. Specimens from Austria, Italy, Hungary, Slovakia, Croatia and Greece have been checked, among them one reared from Trinia glauca, which had been misidentified as A. hippomarathri. A report of A. rotundella from Russia also belongs to this species.